Clinical and non-clinical aspects of reimbursement policy for orphan drugs in selected European countries - Jakubowski, Szczepan; Holko, Przemysław; Nowak, Rafał; Warmuth, Marisa; Dooms, Marc; Salminen, Outi; Cortial, Lucas; Selke, Gisbert W.; Georgi, Christina; Magnússon, Einar; Crisafulli, Salvatore; Strijbosch, Fons; et al. (Frontiers in Pharmacology, 2024)
Objectives The aim of the study was to assess the reimbursement policy for orphan drugs (ODs) in selected European countries in relation to the availability and impact of clinical evidence, health technology assessment (HTA) procedures and reimbursement decision-making. Materials and Methods A list of authorized ODs was extracted from a web-based registry of the European Medicines Agency, including information on active substance, Anatomical Therapeutic Chemical (ATC) classification code, and therapeutic area. A country-based questionnaire survey was conducted between September 2022 and September 2023 among selected experts from 12 European countries. A descriptive and statistical analysis was performed to identify correlations between country characteristic, HTA procedures, drug indication and positive recommendations or reimbursement decisions for ODs. Results Safety assessment for ODs was mandatory in 10 countries, while it was optional in one country (Italy) and not required in one country (Iceland). Efficacy assessment for ODs was mandatory in 11 countries and not required in one country (Iceland). The impact of safety and efficacy assessment on reimbursement decisions was rated as high in 10 countries and as low in one country (Germany). Dedicated OD legislation and policies were reported in seven countries. In two countries (Belgium, Iceland), the HTA was not mandatory, and in one country (Germany), it only had an informative function. A positive recommendation (from an HTA agency or advisory body) guaranteed reimbursement in four countries, while a negative recommendation excluded reimbursement only in one country (Iceland). The proportion of reimbursed ODs ranged from 23.5% in Iceland to 86% in Germany (p < 0.001). ODs with ATC code L represented the largest group of medicines (n = 49). They were also very frequently reimbursed ODs in the countries studied, with a mean of 61.8% (p < 0.001). Conclusion European countries differ in terms of the impact of clinical issues and additional clinical aspects on the reimbursement policy for ODs. Reimbursement decisions were affected by OD-specific legislation, policies, and EMA authorization status. HTA dossiers and procedures significantly influenced reimbursement decisions, although some ODs were reimbursed regardless of the positive or negative recommendations. ATC codes were significantly correlated with reimbursement status and positive recommendation.